Organiziranost slovenskih izseljencev v Braziliji v kulturnih in narodno podpornih društvih - Hlebanja, Neža (Časopis za zgodovino in narodopisje, 2022)
In this article the author discusses the organisation of Slovenian emigrants in Brazil in cultural and national beneficial associations in all periods of the community’s formation, i.e., before the First World War, between the two World Wars, after the Second World War and after Slovenia’s independence. Initially, Slovenian emigrants were members of emigrants’ organisations from the countries of origin – the Habsburg Monarchy, the Kingdom of Yugoslavia and the Republic of Yugoslavia. In the period between both wars, separate Slovene societies appeared alongside the Yugoslav ones. After the independence of Slovenia in 1991, the associations that had existed until then were dissolved according to the ethnic principle. The societies were both cultural and fraternal beneficial organisations.
Keywords: Beritoga; Brazilija; izseljenske organizacije; kulturna društva; migracije; migracijska politika; narodna društva; Naš dom; ORENUS; Primorje; SAIUG; slovenski izseljenci; Zveza Slovencev v Braziliji